Outcomes following percutaneous coronary intervention in patients with cancer. (1st February 2020) - Quintana, Raymundo A.; Monlezun, Dominique J.; Davogustto, Giovanni; Saenz, Humberto R.; Lozano-Ruiz, Francisco; Sueta, Daisuke; Tsujita, Kenichi; Landes, Uri; Denktas, Ali E.; Alam, Mahboob; Paniagua, David; Addison, Daniel; et al.
Abstract: Background: Randomized clinical trials demonstrated the benefits of percutaneous coronary interventions (PCI) in diverse clinical settings. Patients with cancer were not routinely included in these studies. Methods/results: Literature search of PubMed, Cochrane, Medline, SCOPUS, EMBASE, and ClinicalTrials was conducted to identify studies that assessed one-year all-cause, cardiovascular and non-cardiovascular mortality in patients with historical or active cancer. Using the random effects model, we computed risk ratios (RRs) and standardized mean differences and their 95% confidence intervals for the dichotomous and continuous measures and outcomes, respectively. Of 171 articles evaluated in total, 5 eligible studies were included in this meta-analysis. In total, 33, 175 patients receiving PCI were analyzed, of whom 3323 patients had cancer and 29, 852 no cancer history. Patients in the cancer group had greater all-cause mortality [RR 2.22 (1.51–3.26; p < 0.001)], including cardiovascular mortality [RR 1.34 (1.1–1.65; p = 0.005)] and non-cardiovascular mortality [RR 3.42 (1.74–6.74; p ≤ 0.001], at one-year compared to non-cancer patients. Patients in the cancer group had greater one-month all-cause mortality [RR 2.01 (1.24–3.27; p = 0.005)] and greater non-cardiovascular mortality [RR 6.87 (3.10–15.21; p ≤0.001)], but no difference in one-month cardiovascular mortality compared to non-cancer patients. Meta-regression analyses showed that the difference in one-year all-cause and cardiovascular mortality between both groups was not attributable to differences in baseline characteristics, index PCI characteristics, or medications prescribed at discharge. Conclusions: Patients with cancer undergoing PCI have worse mid-term outcomes compared to non-cancer patients. Cancer patients should be managed by a multi-specialist team, in an effort to close the mortality gap. Highlights: First meta-analysis of outcomes after PCI in cancer patients In total, 33, 175 patients receiving PCI were analyzed in this study. Cancer patients were found to have increased risk of 1-year all-cause mortality. Cancer patients have increased risk of 1-year cardiovascular mortality. In meta-regression, 1-year outcomes differences were independent of baseline traits.